Fostering students’ systems thinking through futures education - Hyyppä, Iina; Rasa, Tapio; Laherto, Antti (Frontline Learning Research, 2024)
In an era of worsening environmental crises, students may not perceive themselves as able to impact and change the inevitably upcoming futures. Accordingly, a common goal of educational systems has been to increase students’ agency and sensemaking in a complex world. Simultaneously, students are facing unprecedented levels of futures anxiety, and educational institutions undervalue the importance of future thinking. To take on a constructive approach on futures thinking, we examine how students’ systems thinking skills develop during a futures education course in which they write their own visions of a hopeful future. By looking at the thematic spheres of society, nature, and technology, we analyse how students develop systemic understandings of the complex system that is the context of the study: the city of the future. The study examines how students’ written futures visions develop throughout the course, and how those developments indicate development in systems thinking. The results show that the futures education course allowed students to improve their understandings of the interconnectedness of the topics they raised, fostering more holistic and active understandings of the futures, here shown through the multidimensional development of systems thinking. Students developed a deeper understanding of the interrelationships of society, nature, and technology, and developed understandings of the pathways to change and the agency and action needed to achieve their futures.